Symmetry of postural tone in right homogeneous functional laterality evaluated by Fukuda test - Arabi, Hafid; Adarmouch, Latifa (Acta Biomedica Atenei Parmensis, 2020)
Background: To study the symmetry of postural tone in subjects with right homogeneous functional laterality. Methods: It was an observational study; we looked for the right homogeneous functional laterality by clinical tests on the eyes, feet and hands. Postural tone was evaluated by the Fikuda test. We measured the mean value of the Fikuda angle and in cm walking forward or backward compared to the A axis and the deviation to the left or right compared to the B walking axis. These two axes were perpendicular. Results: There were 80 homogeneous right-hand adult subjects. There were 52 males (63, 52%) and 28 females (36, 47%). The median age was 34, 85 years (23, 42- 47, 57). For the studied population the deviation angle according to Fukuda test was 0° (-15°; 15°), the subjects stepped 81 cm (52; 110) forward without deviation from the B walking axis 0cm (-14; 20). Male subjects remained on the walking axis 0° (-17°, 19°) while stepping 81 cm (51, 119) forward without right-left deviation 0 cm (-17, 19). Female subjects stepped (83 cm (52; 110) forward, and away from the walking axis (3 cm (-23; 21)), without deviation 0° (-17 °; 19 °). Conclusion: The functional homogeneous laterality did not influence postural tone. The lateralization is a complex phenomenon.